The great Recession of 2009: Implications for LAC - Díaz-Bonilla, Eugenio (2009)
Eugenio Díaz Bonilla, Executive Director, Argentina and Haití, IDB 30th April 2009, International Food Policy Research Institute, Washington D.C.